Does it have to be a sacrifice? Different notions of the good life, pro-environmental behavior and their heterogeneous impact on well-being - Martin Binder; Ann-Kathrin Blankenberg; Jorge Guardiola (University of Göttingen, Center for European, Governance and Economic Development Research (cege), 2019)
Our well-being is influenced by our notion of what constitutes a good life, a vital part of our identity. While pro-environmental behavior is often found to be positively related to individuals' well-being, our research delves into the extent to which this relationship is influenced by individuals' identity, measured both as green self-image and their notion of the good life in general. Using survey responses from Spanish university students (n = 640) and paying close attention to the subjective perception of what it means to be "satisfied with their lives", we find that green behavior is negatively related to life satisfaction in our sample. In contrast, green self-image is positively related to life satisfaction. Whether pro-environmental behavior is positively related to life satisfaction further depends on whether one's notion of the good life (and hence happiness) is utopian, stoicist, or based on a fulfillment- or virtueview. In addition, well-being loss from pro-environmental behavior also decreases with the available disposable income.
Keywords: 330; Pro-environmental behavior; subjective well-being; good life; identity; green self-image; conceptual referent theory; life satisfaction